EPIDEMIOLOGY OF DENGUE HAEMORRHAGIC FEVER IN DKI JAKARTA 2017 - 2021 - Saputri, Aliyyah Aswinanda (HIGEIA (Journal of Public Health Research and Development), 2023)
ABSTRACT Dengue is one of the most widespread mosquito-borne disease that infect human with spread over the Americas, Asia, Africa, and Australia every year. In Indonesia, Dengue cases have been reported in 474 districts or cities throughout 34 provinces, with deaths occurring in 203 districts across 29 provinces. In DKI Jakarta Dengue is still a major public health problem as of September 2022 dengue cases in DKI Jakarta have doubled the total cases in 2021 with dengue fever affecting 64 per 100,000 population. This research aims to describe the number of cases, annual morbidity (IR), annual mortality (CFR), and peak incidence as epidemiological understanding of dengue haemorrhagic fever in DKI Jakarta from 2017 to 2021 and during the COVID-19 pandemic. A descriptive study conducted in this research based on secondary data from Ministry of Health, DKI Jakarta Health Office, and Health Profile. The research shows a result in fluctuating of Dengue incidence in DKI Jakarta from 2017 to 2021 with most cases in East Jakarta and peak cases on rainy season. ABSTRAK Dengue adalah salah satu penyakit yang ditularkan oleh nyamuk yang paling luas menginfeksi manusia dengan penyebaran di Amerika, Asia, Afrika, dan Australia setiap tahunnya. Di Indonesia, kasus DBD dilaporkan di 474 kabupaten/kota di 34 provinsi, dengan kematian terjadi di 203 kabupaten di 29 provinsi. Di DKI Jakarta DBD masih menjadi masalah kesehatan masyarakat utama dengan hingga September 2022 kasus DBD di DKI Jakarta meningkat dua kali lipat dari total kasus di tahun 2021 dengan insidensi 64 per 100.000 penduduk. Penelitian ini bertujuan untuk mendeskripsikan jumlah kasus, angka kesakitan tahunan (IR), angka kematian tahunan (CFR), dan puncak kasus sebagai pemahaman epidemiologi demam berdarah dengue di DKI Jakarta tahun 2017 - 2021 dan selama pandemi COVID-19. Studi deskriptif yang dilakukan dalam penelitian ini berdasarkan data sekunder dari Kementerian Kesehatan, Dinas Kesehatan DKI Jakarta, dan Profil Kesehatan. Hasil penelitian menunjukkan adanya fluktuasi kejadian DBD di DKI Jakarta dari tahun 2017 sampai dengan tahun 2021 dengan kasus terbanyak di Jakarta Timur dan puncak kasus pada musim hujan.